Nurse’s Lean Management Practices and Hospital Discharge Time Improvement - Sabilla, Berlianda Nur; Almanfaluthi, Muhammad (Proceedings Series on Health & Medical Sciences, 2025)
Lean management is a dedicated, effective system for resource optimization, time efficiency, waste reduction, and care improvement. We aimed to evaluate the implementation of lean management in our hospital setting. We expect significant improvement in time efficiency, particularly in discharge time, administrative collection, and payment mechanism. We randomly collected 494 patients’ medical records regarding time departure after treatment—308 of 494 representing the period before lean implementation. We performed additional nested randomization stratified by hospital class services (first class, second class, third class, and VIP). The results confirmed substantial time reduction (Mann Whitney test < 0.01 with high effect sizes r-rank biserial = .98) in discharge time in the nursing administration and cashier sections before and after lean implementation. Moreover, these findings were consistent across class services (nested-Mann-Whitney <.0.01). The downward waiting time was visible if the patient was hospitalized in the first, second, third, or VIP class. Implementing lean management reduces to 78% waiting time compared to the period before implementation (95%CI IRR negative binomial regression 77-79%). Lean management practice among nurses slashes patient discharge waiting time by 78%, proving its power to streamline hospital operations and boost efficiency across all service classes.